Virulence Profiles of Wild-Type, P.1 and Delta SARS-CoV-2 Variants in K18-hACE2 Transgenic Mice - da Silva Santos, Yasmin; Gamon, Thais Helena Martins; de Azevedo, Marcela Santiago Pacheco; Telezynski, Bruna Larotonda; de Souza, Edmarcia Elisa; de Oliveira, Danielle Bruna Leal; Dombrowski, Jamille Gregório; Rosa-Fernandes, Livia; Palmisano, Giuseppe; de Moura Carvalho, Leonardo José; Luvizotto, Maria Cecília Rui [UNESP]; Wrenger, Carsten; et al. (MDPI, 2023)
Since December 2019, the world has been experiencing the COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and we now face the emergence of several variants. We aimed to assess the differences between the wild-type (Wt) (Wuhan) strain and the P.1 (Gamma) and Delta variants using infected K18-hACE2 mice. The clinical manifestations, behavior, virus load, pulmonary capacity, and histopathological alterations were analyzed. The P.1-infected mice showed weight loss and more severe clinical manifestations of COVID-19 than the Wt and Delta-infected mice. The respiratory capacity was reduced in the P.1-infected mice compared to the other groups. Pulmonary histological findings demonstrated that a more aggressive disease was generated by the P.1 and Delta variants compared to the Wt strain of the virus. The quantification of the SARS-CoV-2 viral copies varied greatly among the infected mice although it was higher in P.1-infected mice on the day of death. Our data revealed that K18-hACE2 mice infected with the P.1 variant develop a more severe infectious disease than those infected with the other variants, despite the significant heterogeneity among the mice.
Keywords: COVID-19; Delta variant; Gamma variant; K18-hACE2; SARS-CoV-2; variants of concern